The Influence of Problem-Based Learning Model on The Ability of The Problem of Mathematical Stories - Nurmalasari; La Ode Amril; Megan Asri Humaira (Indonesian Journal of Applied Research (IJAR), 2020)
The purpose of this study was to determine the effect of problem-based learning models or problem-based learning models on the ability of students to solve mathematical story problems with learning material in space and flat in class 5 Panaragan State Elementary School 1, Bogor City. The approach used in this research is a quantitative approach with a quasi-experimental method. There are several techniques used in this study, namely observation techniques, interview techniques, and tests. Then obtained research results with the average difference in value between the control class and the experimental class, the experimental class has an average value of 73.11, and the control class has an average value of 60.86. After calculating the t-test (One-Sample Test) on the experimental class's post-test value, the Sign value is known. 0.04, because 0.04 <0.05, then Ha is accepted, and H0 is rejected, which shows the influence of PBL models on the ability to solve students' mathematical story problems.